The influence of the nuclear surface diffuseness on the transition charge densities. - Kosmas, T. S.; Vergados, J. D. (HNPS Advances in Nuclear Physics, 2019)
Proton partial occupancies of the nuclear surface orbits are used in a modified shell model approach to study isoscalar dipole transition charge densities and form factors for self-conjugate nuclei. The energy-weighted sum-rules of Harakeh-Dieperink for both the transition form factor and transition charge density are modified so as fractional occupation probabilities of the states may be used. The partial occupancies of the surface n/j-levels are determined by fitting to the experimental inelastic scattering data and compared with those found previously in the study of nuclear ground state properties